ADL and IADL Following Open-Heart Surgery: The Role of a Character Strength Factor and Preoperative Medical Comorbidities - Ai, Amy L. (Journal of religion and health, 2022)
Open-heart surgery (OHS) is common in late life and is expected to improve functioning despite aging of OHS patients. Few studies have explored the influence of both psychosocial strength factors, metal health, and pre- and peri-OHS medical factors, including cardiac indices, on post-OHS functioning. This study explores the role of character strengths (e.g., hope and spirituality) in post-OHS activities of daily living (ADL) and instrumental ADL (IADL), along with cardiac indices used by all cardio-thoracic surgeons, after controlling for self-reported pre-OHS depression, quality of life indicators, and non-cardiac medical comorbidities. Three waves of interview data and cardiac/surgical indices in the Society of Thoracic Surgeon (STS) national database were collected for a cohort of 481 patients (age = 62 +, female 42%). Multiple linear regression was used to identify pre-OHS predictors of post-OHS functional status. ADL and IADL statuses after OHS were better among those who pursued pre-OHS positive spiritual/religious coping than those who did not. Outcomes were poorer for those reporting poor pre-OHS, higher numbers of medical comorbidities, and use of more post-OHS prayer for coping. Perfusion time, a proxy for surgical complexity, was associated with poor IADL only. Pre-OHS positive spiritual coping, a common coping means used among cardiac patients in medical crises, could have played a positive role in better post-OHS functional status during the post-OHS recovery month. Cardiac health providers should pay more attention to patient-centered character strengths and coping and non-cardiac conditions. More nuanced interdisciplinary research is necessary to identify mechanisms underlying these associations.